Circus Mirandus - Beasley, Cassie (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2015)
When he realizes that his grandfather's stories of an enchanted circus are true, Micah Tuttle sets out to find the mysterious Circus Mirandus--and to use its magic to save his grandfather's life.
710
Keywords: Magic -- Juvenile fiction; Circus -- Juvenile fiction; Grandfathers -- Juvenile fiction; Great-aunts -- Juvenile fiction; Orphans -- Juvenile fiction; Friendship -- Juvenile fiction; Sick -- Juvenile fiction